2015
DOI: 10.1097/cej.0000000000000066
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear dose–response relationship between radon exposure and the risk of lung cancer

Abstract: Although radon exposure (RE) has been confirmed to increase the risk of lung cancer (LC), questions remain about the shape of the dose-response relationship between RE and the risk of LC. We carried out a dose-response meta-analysis to investigate and quantify the potential dose-response association between residential and occupational exposure to radon and the risk of LC. All cohort and case-control studies published in English and Chinese on Embase, PubMed, and China National Knowledge Infrastructure (CNKI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…In contrast, a meta-analysis of 60 publications showed a non-linear association of the dose and response between exposure to environmental Rn and the risk of lung cancer. This increased risk is particularly evident when the cumulative exposure to Rn is well above the recommended concentration limit for a long period of time [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, a meta-analysis of 60 publications showed a non-linear association of the dose and response between exposure to environmental Rn and the risk of lung cancer. This increased risk is particularly evident when the cumulative exposure to Rn is well above the recommended concentration limit for a long period of time [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Exposure to residential radon plays an important role in the genesis of lung cancer, although a complete description of the nature of this role is lacking, despite the publication of recent studies [4] and its classification as the first risk factor for lung cancer in never-smokers [5]. Different meta-analysis and pooling studies have shown a dose-response relationship between radon exposure and lung cancer risk [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…This study reported that the linear dose–response relationship remained significant with no evidence of a threshold when only individuals with radon concentrations of < 200 Bq/m 3 were included. A recent meta-analysis on this issue reported evidence of a nonlinear dose–response relationship between radon exposure and the risk of lung cancer [ 27 ]. Duan et al (2015) concluded that there is a non-linear dose–response relationship between indoor radon and lung cancer risk, but according to the results, a linear dose–response relationship was obvious in the individuals exposed to less than 200 Bq/m 3 of radon, but this incremental relationship was weak in individuals exposed to more than 200 Bq/m 3 of radon.…”
Section: Introductionmentioning
confidence: 99%